Peranan Kelompok Sosial Dalam Membentuk Perilaku Keagamaan Santri SMP Pondok Pesantren Muhammadiyah Boarding School Sleman Yogyakarta - Eka Rinor Maya (LITERASI (Jurnal Ilmu Pendidikan), 2021)
This research amis to obtain information on: (1) Students’ interaction in social groups, (2) roles of social groups in shaping students’ religious behaviour at SMP (Junior High School) MBS Sleman Yogyakarta, (3) students’ religious behaviour resulted from the roles of social groups in shaping their behaviour.This research is a descriptive qualitative study conducted at SMP Muhammadiyah Boarding School Sleman Yogyakarta. The data Wet collected using observation, interview, and documentation.The dinding show that: (1) The interaction of nasheed group is divided into and invovelment stage.the interaction among internal and external members have been included in the contact (introduction) stage, while the involvement stage is only found in the interaction of internal nasheed group. (2) The role among nasheed members, in addition to their roles in improving their singing ability, are also used to facilitate them in improving their spirit of spirituality through organized religious agenda. (3) The nasheed group gives positive impacts to its members in some dimensional namely faith, worship, and practice. The positive impacts in religious dimension for its members are found in their mental and mind development, emotion development, social consideration, moral development as well as attitudde and interest Development. Keywords: Social Group, Religious Behaviour, Students